Islands in the Screen: The Robinsonnade as Television Genre - Heyer, Paul (Cinémas)

(untitled) (Cinémas, 2013)
The island survivor narrative, or robinsonnade, has emerged as a small but significant television genre over the past 50 years. The author considers its origins as a literary genre and the screen adaptations that followed. Emphasis is placed on how “island TV” employed a television aesthetic that ranged from an earlier conventional approach, using three cameras, studio locations, and narrative resolution in each episode, to open-ended storylines employing a cinematic style that exploits the new generation of widescreen televisions, especially with the advent of HDTV. Two case studies centre the argument: Gilligan’s Island as an example of the former, more conventional aesthetic, and Lost as an example of the new approach. Although both series became exceedingly popular, other notable programs are considered, two of which involved Canadian production teams: Swiss Family Robinson and The Mysterious Island. Finally, connections are drawn between robinsonnades and the emerging post-apocalyptic genre as it has moved from cinema to television.